Positive electrode for secondary battery and secondary battery

By integrating small-diameter carbon fibers into the positive electrode active material layer of lithium-ion batteries, the uneven charging and discharge reactions are mitigated, ensuring high cycle characteristics and energy density despite high nickel content.

JP7624610B2Active Publication Date: 2025-01-31PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022503697
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-28
Filing Date
2021-02-25
Publication Date
2025-01-31
Estimated Expiration
2041-02-25

AI Technical Summary

Technical Problem

Lithium-ion secondary batteries face issues with uneven charging and discharge reactions due to the use of lithium-transition metal composite oxides, leading to reduced cycle characteristics and instability in the crystal structure, especially when the nickel content is increased.

Method used

Incorporating a small amount of carbon fibers with a diameter of 5 nm or less into the positive electrode active material layer, which acts as a conductive agent, forms a conductive path between particles, reducing potential variations and suppressing unevenness in the charging reaction, while maintaining a high nickel content to enhance capacity.

Benefits of technology

This approach maintains high cycle characteristics and energy density by minimizing unevenness in the charging reaction, even with increased nickel content, allowing for a high-capacity positive electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624610000002
    Figure 0007624610000002
  • Figure 0007624610000001
    Figure 0007624610000001
Patent Text Reader

Abstract

This positive electrode for secondary batteries is provided with a positive electrode collector and a positive electrode mixture layer that is arranged on the surface of the positive electrode collector, while containing a positive electrode active material. The positive electrode active material contains a lithium-containing composite oxide wherein 80% by atom or more of the metals other than lithium is nickel, said composite oxide having a layered structure. The positive electrode mixture layer contains carbon fibers having an outermost peripheral diameter of 5 nm or less; and the carbon fibers are contained at a ratio of 0.1 part by mass or less relative to 100 parts by mass of the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to secondary batteries, and more particularly to improvements in positive electrodes used in secondary batteries. [Background technology]

[0002] Secondary batteries, especially lithium-ion secondary batteries, have high output and high energy density, and are expected to be used for small consumer applications, power storage devices, and power sources for electric vehicles. A composite oxide of lithium and a transition metal (e.g., cobalt) is used as the positive electrode active material for lithium-ion secondary batteries. By replacing part of the cobalt with nickel, it is possible to increase the capacity.

[0003] Furthermore, in recent years, in order to increase the energy density and durability of lithium-ion batteries, attempts have been made to use a positive electrode active material with a large charge / discharge capacity in the positive electrode and to compress a large amount of the positive electrode active material to increase the amount of positive electrode active material per unit area.

[0004] In Patent Document 1, in a lithium ion secondary battery, Li y Ni (1-x) M x and carbon nanotubes in the positive electrode, and a / b, which is the ratio of the average length a of the carbon nanotubes to the average particle size b of the primary particles of the lithium nickel composite oxide, is set to 0.5 or more. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2008 / 051667 Brochure Summary of the Invention

[0006] In the examples of Patent Document 1, it is described that the use of carbon nanotubes with a large diameter of about 20 nm improves the cycle characteristics of lithium ion batteries. However, when a large amount of positive electrode active material used in high capacity batteries is loaded and a positive electrode formed by compression is used with carbon nanotubes with a large diameter of about 20 nm, the electrochemical reaction is likely to be non-uniform. Therefore, unevenness is likely to occur in the charge and discharge reaction in the positive electrode. As a result, the cycle characteristics are likely to deteriorate.

[0007] In particular, when a lithium-transition metal composite oxide is used as the positive electrode active material and the Ni ratio in the lithium-transition metal composite oxide is increased in order to obtain a high capacity, if unevenness occurs in the charge / discharge reaction in a part of the positive electrode region, the crystal structure in that part of the region may change to a structure that makes it difficult to absorb and release Li ions due to excessive Li extraction. As a result, the deterioration of cycle characteristics is likely to become significant.

[0008] One aspect of the present disclosure relates to a positive electrode for a secondary battery, comprising: a positive electrode current collector; and a positive electrode mixture layer containing a positive electrode active material and provided on a surface of the positive electrode current collector, wherein the positive electrode active material has a layered structure and contains a lithium-containing composite oxide in which 80 atomic % or more of metals other than lithium are nickel, and the positive electrode mixture layer contains carbon fibers having an outermost peripheral diameter of 5 nm or less, and the carbon fibers are contained in a proportion of 0.1 part by mass or less relative to 100 parts by mass of the positive electrode active material.

[0009] Another aspect of the present disclosure relates to a secondary battery including the above-mentioned positive electrode for secondary battery, a separator, a negative electrode facing the positive electrode for secondary battery with the separator interposed therebetween, and an electrolyte.

[0010] According to the present disclosure, a secondary battery that achieves both high energy density and high cycle characteristics can be realized. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic perspective view, with a portion cut away, of a secondary battery according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The positive electrode for a secondary battery according to an embodiment of the present disclosure includes a positive electrode current collector and a positive electrode mixture layer including a positive electrode active material and provided on the surface of the positive electrode current collector. The positive electrode active material includes a lithium-containing composite oxide having a layered structure and containing nickel in an amount of 80 atomic % or more of the metal other than lithium. The positive electrode mixture layer includes carbon fibers having an outer diameter of 5 nm or less.

[0013] According to the positive electrode for a secondary battery of this embodiment, since a small amount of carbon fibers having a small outer diameter are contained in the positive electrode mixture layer, the liquid circulation property can be improved, and even when a lithium-containing metal oxide having a Ni ratio of 0.8 or more is used as the positive electrode active material, the cycle characteristics can be maintained at a high level.

[0014] The carbon fiber can be added to the positive electrode mixture layer as a conductive agent for forming a conductive path between particles of the positive electrode active material and increasing the conductivity of the positive electrode mixture layer. The fiber length of the carbon fiber can include, for example, 1 μm or more. That is, the aspect ratio of the carbon fiber (ratio of fiber length to outer diameter of the fiber) is extremely large. By interposing the carbon fiber with excellent conductivity between the particles of the positive electrode active material, the potential variation between the positive electrode active material particles is reduced, and the unevenness of the charge and discharge reaction is suppressed. Furthermore, since the carbon fiber with a large aspect ratio occupies a small volume in the positive electrode mixture layer, the carbon fiber is prevented from interposing in the gap between the positive electrode active material particles that should be filled with the electrolyte, thereby preventing the liquid circulation from being reduced. In addition, because it is fibrous, the gap for the electrolyte can be easily secured even when the positive electrode active material is densely arranged in the positive electrode mixture layer. As a result, the deterioration of the cycle characteristics can be significantly suppressed.

[0015] In addition, since the carbon fibers occupy only a small volume in the positive electrode mixture layer, most of the space occupied by the positive electrode mixture layer excluding the carbon fibers can be occupied by the positive electrode active material. Therefore, a high-capacity positive electrode can be easily obtained by increasing the thickness of the positive electrode mixture layer and / or increasing the amount of positive electrode active material per positive electrode area by compression.

[0016] The carbon fiber content may be 0.1 parts by mass or less relative to 100 parts by mass of the positive electrode active material. The carbon fiber content may be 0.01 parts by mass or more and 0.1 parts by mass or less, 0.02 parts by mass or more and 0.1 parts by mass or less, or 0.02 parts by mass or more and 0.05 parts by mass or less relative to 100 parts by mass of the positive electrode active material. The carbon fiber content is a value based on the mass of the positive electrode active material in a discharged state.

[0017] The content ratio of the positive electrode active material in the positive electrode mixture layer is determined from a mixture sample obtained by dismantling a discharged secondary battery, washing the obtained positive electrode with an organic solvent, and peeling off only the mixture layer after vacuum drying. The ratio of the binder component and the conductive material component other than the positive electrode active material can be calculated by subjecting the mixture sample to thermal analysis such as TG-DTA. When the binder component and the conductive material component contain multiple types of carbon materials, the ratio of carbon fiber among them can be calculated by performing microscopic Raman spectroscopy on the cross section of the positive electrode mixture layer.

[0018] The outer diameter and fiber length of carbon fibers are determined by image analysis using a scanning electron microscope (SEM). For example, the fiber length is determined by measuring the length and diameter of a number of randomly selected carbon fibers (e.g., about 100 to 1000 fibers) and averaging the measured values. The fiber length of carbon fibers refers to the length when the fibers are linear.

[0019] The carbon fiber may be, for example, a carbon nanotube. The carbon nanotube may be single-walled, double-walled, or multi-walled, but since a small amount can provide a large effect, single-walled carbon nanotubes are preferred. Carbon nanotubes with a fiber diameter of 5 nm or less contain a large amount of single-walled carbon nanotubes. Single-walled carbon nanotubes may account for 50 mass% or more of the total carbon nanotubes. The fiber length of the carbon fiber is preferably 1 μm or more from the viewpoint of ensuring electronic conduction inside the positive electrode. On the other hand, there is no upper limit to the fiber length as long as the fiber is appropriately arranged inside the positive electrode, but considering that the particle diameter of the positive electrode active material is generally 1 μm or more and 20 μm or less, a length equivalent to that is considered to be appropriate. That is, the fiber length of the carbon fiber may be, for example, 1 μm or more and 20 μm or less. For example, when a plurality of carbon fibers (e.g., 100 or more) are arbitrarily selected in the positive electrode mixture layer, the fiber length of 50% or more of the carbon fibers may be 1 μm or more, or may be 1 μm or more and 20 μm or less, and the fiber length of 80% or more of the carbon fibers may be 1 μm or more, or may be 1 μm or more and 20 μm or less.

[0020] In order to obtain high capacity, the amount of the positive electrode mixture layer per unit area on the surface of the positive electrode current collector is set to 250 g / m 2 According to this embodiment, even when the amount of the positive electrode mixture and the amount of the positive electrode active material are increased in this way, unevenness in the charge / discharge reaction is suppressed, and deterioration of the cycle characteristics is suppressed.

[0021] In addition, in order to obtain a high capacity, the positive electrode active material may have a nickel ratio of 85 atomic % or more among metals other than lithium in the lithium-containing composite oxide. According to this embodiment, even when the Ni ratio of the positive electrode active material is increased in this way, unevenness in the charge / discharge reaction is suppressed, and deterioration of cycle characteristics is suppressed.

[0022] Next, the secondary battery according to the embodiment of the present disclosure will be described in detail. The secondary battery includes, for example, a positive electrode, a negative electrode, an electrolytic solution, and a separator as follows.

[0023] [Positive Electrode] The positive electrode includes a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector and containing a positive electrode active material. As the positive electrode, the above-described positive electrode for a secondary battery is used. The positive electrode mixture layer can be formed, for example, by applying a positive electrode slurry in which a positive electrode mixture containing a positive electrode active material, a binder, etc. is dispersed in a dispersion medium onto the surface of the positive electrode current collector and drying it. The dried coating film may be rolled if necessary. The positive electrode mixture layer may be formed on one surface of the positive electrode current collector or on both surfaces.

[0024] The positive electrode mixture layer contains, as essential components, a positive electrode active material and carbon fibers having an outermost peripheral diameter of 5 nm or less. The carbon fibers having an outermost peripheral diameter of 5 nm or less are included in the positive electrode mixture layer as a conductive agent. Another conductive agent different from the carbon fibers having an outermost peripheral diameter of 5 nm or less may be included in the positive electrode mixture layer. The positive electrode mixture layer can contain, as optional components, a binder, a thickener, etc. Known materials can be used as the binder, the thickener, and another conductive agent.

[0025] As the positive electrode active material, a lithium-containing composite oxide having a layered structure (for example, a rock salt-type crystal structure) containing lithium and a transition metal can be used. Specifically, the lithium-containing composite oxide can be, for example, Li a Ni x M 1-x O2 (where 0 < a ≤ 1.2, 0.8 ≤ x < 1, and M includes at least one selected from the group consisting of Co, Al, Mn, Fe, Ti, Sr, Na, Mg, Ca, Sc, Y, Cu, Zn, Cr, and B). It may be a lithium-nickel composite oxide represented by. Among them, M preferably includes at least one selected from the group consisting of Co, Mn, and Fe. From the viewpoint of the stability of the crystal structure, Al may be included as M. Note that the a value indicating the molar ratio of lithium increases or decreases by charge and discharge. As a specific example of such a composite oxide, lithium-nickel-cobalt-aluminum composite oxide (LiNi0.9 Co 0.05 Al 0.05 O2, etc.

[0026] The lithium-nickel composite oxide can extract more lithium ions from the lithium-nickel composite oxide during charging as the Ni ratio x increases, and the capacity can be increased. However, the valence of Ni in the lithium-nickel composite oxide with increased capacity tends to be higher. As a result, the crystal structure is likely to become unstable, particularly in a fully charged state, and is likely to change (become inactive) to a crystal structure that makes it difficult to reversibly absorb and release lithium ions due to repeated charging and discharging. As a result, the cycle characteristics are likely to deteriorate. In particular, when a configuration is adopted in which the thickness of the positive electrode mixture layer is increased and / or the mixture layer is compressed to increase the amount of positive electrode active material per area, the flow of lithium ions and / or electrons is likely to be hindered during the charge and discharge reaction, and unevenness is likely to occur in the charge and discharge reaction. When unevenness occurs in the charge and discharge reaction, the crystal structure may become inactive in some areas where the charge reaction has progressed excessively and the amount of lithium ions extracted is large, and the cycle characteristics may deteriorate.

[0027] However, in the positive electrode for secondary batteries of this embodiment, the positive electrode mixture layer contains carbon fibers having an outermost diameter of 5 nm or less, so that the loading amount (coating amount) per unit area of ​​the positive electrode mixture layer can be reduced (for example, 250 g / m 2 Even when the Ni ratio x is increased to 100%, the unevenness of the charge / discharge reaction is suppressed. Therefore, even when a lithium-containing composite oxide having a large Ni ratio x is used, the deterioration of the cycle characteristics is suppressed. Therefore, a secondary battery having excellent cycle characteristics and high energy density can be realized.

[0028] From the viewpoint of obtaining a high capacity, the Ni ratio x in the lithium-containing composite oxide may be 0.85 or more (x≧0.85) or may be 0.9 or more (x≧0.9).

[0029] The shape and thickness of the positive electrode current collector can be selected from the shape and range corresponding to those of the negative electrode current collector. Examples of the material of the positive electrode current collector include stainless steel, aluminum, aluminum alloy, and titanium.

[0030] [Negative electrode] The negative electrode includes, for example, a negative electrode current collector and a negative electrode active material layer formed on the surface of the negative electrode current collector. The negative electrode active material layer can be formed, for example, by applying a negative electrode slurry in which a negative electrode mixture containing a negative electrode active material, a binder, etc. is dispersed in a dispersion medium to the surface of the negative electrode current collector and drying it. The coating film after drying may be rolled as necessary. That is, the negative electrode active material may be a mixture layer. Also, a lithium metal foil or a lithium alloy foil may be attached to the negative electrode current collector. The negative electrode active material layer may be formed on one surface of the negative electrode current collector, or on both surfaces.

[0031] The negative electrode active material layer contains a negative electrode active material as an essential component, and may contain, as optional components, a binder, a conductive agent, a thickener, etc. As the binder, the conductive agent, and the thickener, known materials can be used.

[0032] The negative electrode active material includes a material that electrochemically absorbs and releases lithium ions, lithium metal, and / or a lithium alloy. As the material that electrochemically absorbs and releases lithium ions, a carbon material, an alloy material, and the like are used. As the carbon material, for example, graphite, graphitizable carbon (soft carbon), and non-graphitizable carbon (hard carbon) can be exemplified. Among them, graphite is preferable because of its excellent charge / discharge stability and small irreversible capacity. As the alloy material, there can be mentioned a material that contains at least one metal that can form an alloy with lithium, such as silicon, tin, silicon alloy, tin alloy, and silicon compound. These may be bonded with oxygen to form silicon oxide, tin oxide, and the like.

[0033] As the alloy-based material containing silicon, for example, a lithium ion conductive phase and a silicon composite material in which silicon particles are dispersed in the lithium ion conductive phase can be used. As the lithium ion conductive phase, for example, a silicon oxide phase, a silicate phase, and / or a carbon phase can be used. The main component of the silicon oxide phase (for example, 95 to 100 mass%) can be silicon dioxide. Among them, a composite material composed of a silicate phase and silicon particles dispersed in the silicate phase is preferable in terms of high capacity and small irreversible capacity.

[0034] The silicate phase may contain at least one element selected from the group consisting of Group 1 and Group 2 elements of the long periodic table. Examples of Group 1 elements of the long periodic table and Group 2 elements of the long periodic table include lithium (Li), potassium (K), sodium (Na), magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba). Other elements may include aluminum (Al), boron (B), lanthanum (La), phosphorus (P), zirconium (Zr), and titanium (Ti). Among these, a silicate phase containing lithium (hereinafter also referred to as a lithium silicate phase) is preferred because of its small irreversible capacity and high initial charge / discharge efficiency.

[0035] The lithium silicate phase may be an oxide phase containing lithium (Li), silicon (Si), and oxygen (O), and may contain other elements. The atomic ratio of O to Si in the lithium silicate phase: O / Si is, for example, greater than 2 and less than 4. Preferably, O / Si is greater than 2 and less than 3. The atomic ratio of Li to Si in the lithium silicate phase: Li / Si is, for example, greater than 0 and less than 4. The lithium silicate phase is represented by the formula: Li 2z SiO 2+zIt may have a composition represented by (0 < z < 2). It is preferable that z satisfies the relationship of 0 < z < 1, and more preferably z = 1 / 2. Examples of elements other than Li, Si, and O that may be included in the lithium silicate phase include iron (Fe), chromium (Cr), nickel (Ni), manganese (Mn), copper (Cu), molybdenum (Mo), zinc (Zn), aluminum (Al), and the like.

[0036] The carbon phase can be composed of, for example, low-crystalline amorphous carbon (i.e., amorphous carbon). The amorphous carbon may be, for example, hard carbon, soft carbon, or the like.

[0037] As the negative electrode current collector, a non-porous conductive substrate (such as a metal foil) or a porous conductive substrate (such as a mesh body, a net body, a punching sheet, etc.) is used. Examples of the material of the negative electrode current collector include stainless steel, nickel, nickel alloy, copper, copper alloy, and the like.

[0038] [Electrolyte solution] The electrolyte solution contains a solvent and a solute dissolved in the solvent. The solute is an electrolyte salt that dissociates into ions in the electrolyte solution. The solute may contain, for example, a lithium salt. Components of the electrolyte solution other than the solvent and the solute are additives. The electrolyte solution may contain various additives.

[0039] The solvent is an aqueous solvent or a non-aqueous solvent. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, cyclic carboxylates, and chain carboxylates. Examples of the cyclic carbonates include propylene carbonate (PC), ethylene carbonate (EC), and vinylene carbonate (VC). Examples of the chain carbonates include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). Examples of the cyclic carboxylates include γ-butyrolactone (GBL), and γ-valerolactone (GVL). Examples of the chain carboxylates include methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate (EP). The non-aqueous solvents may be used alone or in combination of two or more.

[0040] Other examples of the non-aqueous solvent include cyclic ethers, chain ethers, nitriles such as acetonitrile, and amides such as dimethylformamide.

[0041] Examples of cyclic ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, crown ethers, and the like.

[0042] Examples of chain ethers include 1,2-dimethoxyethane, dimethyl ether, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.

[0043] These solvents may be fluorinated solvents in which some of the hydrogen atoms are replaced with fluorine atoms. As the fluorinated solvent, fluoroethylene carbonate (FEC) may be used.

[0044] Examples of lithium salts include lithium salts of chlorine-containing acids (LiClO4, LiAlCl4, LiB 10 Cl 10 etc.), lithium salts of fluorine-containing acids (LiPF6, LiPF2O2, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), lithium salts of fluorine-containing acid imides (LiN(FSO2)2, LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc.), lithium halides (LiCl, LiBr, LiI, etc.), etc., can be used. One type of lithium salt may be used alone, or two or more types may be used in combination.

[0045] The concentration of the lithium salt in the electrolyte may be 1 mol / L or more and 2 mol / L or less, or 1 mol / L or more and 1.5 mol / L or less. By controlling the lithium salt concentration within the above range, an electrolyte having excellent ion conductivity and appropriate viscosity can be obtained. However, the lithium salt concentration is not limited to the above.

[0046] The electrolyte may contain other known additives, such as 1,3-propane sultone, methylbenzenesulfonate, cyclohexylbenzene, biphenyl, diphenyl ether, and fluorobenzene.

[0047] [Separator] A separator is interposed between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation. As the separator, a microporous thin film, a woven fabric, a nonwoven fabric, etc. can be used. As the material of the separator, polyolefin such as polypropylene and polyethylene is preferable.

[0048] An example of the structure of the secondary battery is a structure in which an electrode group formed by winding a positive electrode and a negative electrode with a separator interposed therebetween and a non-aqueous electrolyte are housed in an exterior body. Alternatively, instead of a wound type electrode group, other types of electrode groups may be used, such as a stacked type electrode group formed by stacking a positive electrode and a negative electrode with a separator interposed therebetween. The secondary battery may be in any form, such as a cylindrical type, a square type, a coin type, a button type, or a laminate type.

[0049] FIG. 1 is a schematic perspective view, with a portion cut away, of a prismatic secondary battery according to an embodiment of the present disclosure.

[0050] The nonaqueous electrolyte secondary battery 1 includes a bottomed prismatic battery case 11, and an electrode group 10 and a nonaqueous electrolyte housed within the battery case 11. The electrode group 10 includes a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator interposed between them to prevent direct contact. The electrode group 10 is formed by winding the negative electrode, the positive electrode, and the separator around a flat plate-shaped winding core and removing the winding core.

[0051] One end of the negative electrode lead 15 is attached to the negative electrode current collector of the negative electrode by welding or the like. One end of the positive electrode lead 14 is attached to the positive electrode current collector of the positive electrode by welding or the like. The other end of the negative electrode lead 15 is electrically connected to the negative electrode terminal 13 provided on the sealing plate 12. A gasket 16 is disposed between the sealing plate 12 and the negative electrode terminal 13 to insulate them from each other. The other end of the positive electrode lead 14 is connected to the sealing plate 12 and electrically connected to the battery case 11 which also serves as the positive electrode terminal. A resin frame 18 is disposed on the upper part of the electrode group 10 to separate the electrode group 10 from the sealing plate 12 and to separate the negative electrode lead 15 from the battery case 11. The opening of the battery case 11 is sealed with the sealing plate 12. A liquid injection hole 17a is formed in the sealing plate 12, and an electrolyte is injected into the square battery case 11 from the liquid injection hole 17a. Thereafter, the liquid injection hole 17 a is closed with a plug 17 .

[0052] The structure of the secondary battery may be a cylindrical, coin, button, or other shape having a metal battery case, or may be a laminated battery having a battery case made of a laminate sheet that is a laminate of a barrier layer and a resin sheet. In the present disclosure, the type, shape, and the like of the secondary battery are not particularly limited.

[0053] Hereinafter, the present disclosure will be specifically described based on examples and comparative examples, but the present disclosure is not limited to the following examples.

[0054] <Examples 1 to 7> [Preparation of negative electrode] A silicon composite material and graphite were mixed in a mass ratio of 5:95 to be used as the negative electrode active material. The negative electrode active material, sodium carboxymethylcellulose (CMC-Na), styrene-butadiene rubber (SBR), and water were mixed in a predetermined mass ratio to prepare a negative electrode slurry. Next, the negative electrode slurry was applied to the surface of copper foil, which is a negative electrode current collector, and the coating was dried and then rolled to form a negative electrode mixture layer on both sides of the copper foil.

[0055] [Preparation of positive electrode] The lithium-containing composite oxide shown in Table 1 was used as the positive electrode active material. The positive electrode active material, carbon nanotubes (CNT), polyvinylidene fluoride, and N-methyl-2-pyrrolidone (NMP) were mixed in a predetermined mass ratio to prepare a positive electrode slurry. Next, the positive electrode slurry was applied to the surface of an aluminum foil serving as a positive electrode current collector, and the coating was dried and then rolled to form a positive electrode mixture layer on both sides of the aluminum foil. The carbon nanotubes used had an average diameter of about 1.5 nm and a length of about 1 μm to 5 μm.

[0056] [Preparation of electrolyte] An electrolyte was prepared by adding LiPF6 as a lithium salt to a mixed solvent containing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7. The concentration of LiPF6 in the non-aqueous electrolyte was 1.0 mol / L.

[0057] [Preparation of secondary battery] A lead tab was attached to each electrode, and the positive and negative electrodes were spirally wound with a separator between them so that the leads were located at the outermost periphery to prepare an electrode group. The electrode group was inserted into an exterior body made of a laminate film with an aluminum foil barrier layer, and vacuum dried at 105°C for 2 hours. After that, a nonaqueous electrolyte was injected and the opening of the exterior body was sealed to obtain a secondary battery.

[0058] <Comparative Examples 1 to 4> In the preparation of the positive electrode, particulate acetylene black (average particle size: about 20 nm) (AB) was added instead of carbon nanotubes to prepare a positive electrode slurry.

[0059] Other than that, the secondary battery was fabricated in the same manner as in the example.

[0060] Table 1 shows the composition of the lithium-containing composite oxide used as the positive electrode active material, the amount of conductive agent (carbon nanotube or acetylene black) added, and the coating amount and density per unit area of ​​the positive electrode mixture layer in Examples 1 to 7 and Comparative Examples 1 to 4. In Table 1, Batteries A1 to A7 correspond to Examples 1 to 6, and Batteries B1 to B4 correspond to Comparative Examples 1 to 4, respectively.

[0061] [evaluation] (Initial charge / discharge) After completion, each battery was placed in a 25°C environment and charged at a constant current of 0.5 It until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached 0.02 It. After that, constant current discharge was performed at a current of 1.0 It until the voltage reached 2.5 V, and the initial capacity C0 was calculated. Charge and discharge were performed in a 25°C environment.

[0062] (Capacity deterioration amount) The rest period between charging and discharging was 10 minutes, and charging and discharging was repeated 30 cycles under the above charge and discharge conditions in an environment of 25°C, and the discharge capacity C1 at the 100th cycle was calculated. The ratio R1 = C1 / C0 of the discharge capacity C1 to the initial discharge capacity C0 was defined as the capacity retention rate, and the deterioration amount D of each battery was calculated as x D x =1-R1.

[0063] Table 1 shows the amount of capacity deterioration in the batteries A1 to A7 and B1 to B4. x The ratio D1, where D1 is taken as 100, is shown together with the configuration of the positive electrode active material and conductive agent in each battery, and the density of the positive electrode mixture layer. Table 1 shows that batteries A1 to A7, which contain a small amount of carbon nanotubes as carbon fibers with an outermost diameter of 5 nm or less, were able to suppress the increase in capacity deterioration D1 compared to batteries B1 to B4, which contain non-fibrous acetylene black instead of carbon nanotubes.

[0064] Comparing batteries B2 and B3, B2, which has a larger volume density of the positive electrode mixture layer, has a larger capacity degradation amount D1. This is thought to be because B2 has a thinner positive electrode mixture layer than B3, which reduces the liquid circulation and makes it easier for unevenness to occur in the charge and discharge reaction. Also, comparing batteries B2 and B4, B2, which has a larger amount of positive electrode mixture layer applied, has a larger capacity degradation amount D1. This is thought to be because B2 has a larger amount of positive electrode active material than B4 and the positive electrode mixture layer is also thicker, making it easier for unevenness to occur in the charge and discharge reaction.

[0065] In contrast, when comparing batteries A2 and A5, the amount of capacity deterioration was kept low even in A2, which had a large volume density of the positive electrode mixture layer, and when comparing batteries A3 and A4, the amount of capacity deterioration was kept low even in A3, which had a large amount of application of the positive electrode mixture layer.

[0066] [Table 1] [Industrial Applicability]

[0067] According to the secondary battery of the present disclosure, it is possible to provide a secondary battery having high capacity and excellent cycle characteristics. The secondary battery of the present disclosure is useful as a main power source for mobile communication devices, portable electronic devices, and the like. [Explanation of symbols]

[0068] 1 Nonaqueous electrolyte secondary battery 10 electrode groups 11 Battery case 12 Sealing plate 13 Negative terminal 14 Positive lead 15 Negative lead 16 Gasket 17 Sealing 17a Liquid injection hole 18 Frame

Claims

1. a positive electrode current collector; and a positive electrode mixture layer including a positive electrode active material and provided on a surface of the positive electrode current collector, the positive electrode active material includes a lithium-containing composite oxide having a layered structure and containing nickel in an amount of 80 atomic % or more of metals other than lithium, The lithium-containing composite oxide is a lithium-nickel composite oxide represented by a chemical formula Li a Ni x M 1-x O 2 (wherein 0<a≦1.2, 0.8≦x<1, and M includes at least one selected from the group consisting of Co, Al, Mn, Fe, Ti, Sr, Na, Mg, Ca, Sc, Y, Cu, Zn, Cr, and B), the positive electrode mixture layer contains carbon fibers having an outermost peripheral diameter of 5 nm or less, and the carbon fibers are contained in a ratio of 0.1 parts by mass or less relative to 100 parts by mass of the positive electrode active material, The positive electrode for a secondary battery, wherein the positive electrode mixture layer is provided on the surface of the positive electrode current collector with a loading of 250 g / m 2 or more.

2. The positive electrode for a secondary battery according to claim 1 , wherein the positive electrode mixture layer contains the carbon fibers having a fiber length of 1 μm or more.

3. 3. The positive electrode for a secondary battery according to claim 1, wherein the content of the carbon fiber is 0.01 parts by mass or more and 0.05 parts by mass or less with respect to 100 parts by mass of the positive electrode active material.

4. The positive electrode for a secondary battery according to any one of claims 1 to 3, wherein in the chemical formula, x ≧ 0.

85.

5. The positive electrode for secondary batteries according to any one of claims 1 to 4, wherein the carbon fibers contain single-walled carbon nanotubes.

6. The positive electrode for a secondary battery according to any one of claims 1 to 5, wherein in the chemical formula, M includes at least one selected from the group consisting of Co, Mn, and Fe.

7. The positive electrode for a secondary battery according to claim 1, wherein, in the chemical formula, M contains at least Al.

8. The positive electrode for a secondary battery according to claim 1, wherein in the chemical formula, M includes Co and Al.

9. A positive electrode for a secondary battery according to any one of claims 1 to 8, A secondary battery comprising: a separator; a negative electrode facing the positive electrode for the secondary battery with the separator interposed therebetween; and an electrolyte.

10. the negative electrode includes a negative electrode current collector and a negative electrode active material layer including a negative electrode active material and formed on a surface of the negative electrode current collector; The secondary battery according to claim 9 , wherein the negative electrode active material comprises a silicon composite material.

Citation Information

Patent Citations

  • Cathode for lithium based battery and lithium based battery using it

    JP2006086116A

  • Positive electrode mixture slurry, positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    JP2017182989A

  • Apparatus, and associated method, for providing an electronic storage box for securely storing data in electronic form

    WO2008051667A2